Molecular diagnostics : current research and applications - Huggett, Jim F. (Caister Academic Press, 2014)
The application of molecular technology in clinical diagnosis is a rapidly developing area and is predicted to greatly improve the speed, efficiency, and accuracy of diagnostic medicine. The editors of this book have commissioned an excellent series of chapters representing two key molecular diagnostic areas: cancer and infectious diseases. The cancer section deals with the challenges in identifying genetic, epigenetic, and transcriptomic biomarkers. The infectious disease section describes the current clinical applications of molecular diagnostics for the detection of viral, bacterial, and fu.